Peningkatan Kompetensi Guru dalam Pelaksanaan Pembelajaran dengan Pemanfaatan TIK Melalui Bimbingan Belajar di UPTD SDN Madupat 3 Kecamatan CamplongKabupaten Sampang Tahun Pelajaran 2022/2023 - Akhmad Mardiyanto (Departement of Mathematics Education, 2023)
In making teacher learning media easier with the existence of information and communication technology. This research is based on the problems (1) Is Information and Communication Technology (ICT) tutoring by school principals able to increase teacher competence in the use of Information and Communication Technology (ICT). (2) Can the use of Information and Communication Technology help teachers in implementing learning at UPTD SDN Madupat 3, Camplong District, Sampang Regency. (3) How is the competence of teachers in the use of Information and Communication Technology (ICT) at UPTD SDN Madupat 3, Camplong District, Sampang Regency. This research was conducted at UPTD SDN Madupat 3, Camplong District, Sampang Regency. The subjects in this study were 14 teachers, 10 class teachers, 3 sports teachers and 2 religion teachers. Data collection is done through observation and documentation techniques. The results of the study showed that through tutoring the teachers at UPTD SDN Madupat 3, Camplong District, Sampang Regency were able to operate computers properly so they could use Microsoft Office in their studies. The teacher shows seriousness in learning to use Microsoft Office from the researcher. This information the researchers obtained from observations when conducting interviews and guidance to teachers. This tutoring can also increase teacher competency in the use of ICT. This can be proven from the results of observations which show that there is an increase in teacher competence in the use of ICT from cycle to cycle